Biobased thiol-epoxy shape memory networks from gallic acid and vegetable oils. (March 2019) - Feng, Yechang; Hu, Yang; Man, Limin; Yuan, Teng; Zhang, Chaoqun; Yang, Zhuohong
Graphical abstract: Highlights: Biobased thiol-epoxy network was obtained from gallic acid-based thiol. The resulting network has comparable shape memory properties to the petroleum ones. Epoxidized vegetable oils were incorporated into the thiol-epoxy networks. The introduction of vegetable oils has no impact to the shape-fixity ratio. Abstract: Shape memory polymers play an increasingly significant role in the fields of electronics, aerospace and medical science. However, the most of shape memory polymers are derived from petroleum resource nowadays. Herein, biobased thiol-epoxy shape memory network was obtained from gallic acid-based thiol and diglycidyl ether of bisphenol A (DGEBA). The resulting network shows good shape memory performance with the shape-fixity ratio of 98.7%, shape-recovery ratio of 97.7% and excellent cycle stability, which is comparable to the petroleum counterparts. Further, epoxidized vegetable oils were incorporated into the above thiol-epoxy network to investigate the effect of epoxidized vegetable oils on the properties of the resulting networks. After introducing the vegetable oils, shape-fixity ratios show irrelevance with the network structures and keep above 96%. Shape-recovery ratio declines with the increase of epoxidized linseed oil (ELO) contents, but when ELO content equals to 20 wt% of DGEBA, shape-recovery speed enhances compared to the network without epoxidized vegetable oils. This is the first attempt to fabricate the thiol-epoxy shape memory networks from renewable biomasses.